Composition of betel specific chemicals in saliva during betel chewing for the identification of biomarkers. (June 2015) - Franke, Adrian A.; Mendez, Ana Joy; Lai, Jennifer F.; Arat-Cabading, Celine; Li, Xingnan; Custer, Laurie J.
Highlights: Main compounds in betel nuts and saliva from subjects chewing the nuts were guvacine, arecoline, guvacoline and arecaidine. The main compound in the Piper betle leaf and saliva from those chewing the leaf was the allyl benzene compound chavibetol. We found salivary chemical patterns during chewing to identify the 3 most common betel preparations consumed in Guam. Significant increases in baseline saliva levels during chewing for main betel and nicotine alkaloids, as well as chavibetol. Abstract: Betel nut chewing causes cancer in humans, including strong associations with head and neck cancer in Guam. In the search for biomarkers of betel chewing we sought to identify chemicals specific for the 3 most commonly consumed betel preparations in Guam: nut ('BN'), nut + Piper betle leaf ('BL'), and betel quid ('BQ') consisting of nut + lime + tobacco + Piper betle leaf. Chemicals were extracted from the chewing material and saliva of subjects chewing these betel preparations. Saliva analysis involved protein precipitation with acetonitrile, dilution with formic acid followed by LCMS analysis. Baseline and chewing saliva levels were compared using t-tests and differences between groups were compared by ANOVA; p < 0.05 indicated significance. Predominant compounds in chewing material were guvacine, arecoline, guvacoline, arecaidine, chavibetol, and nicotine. In chewing saliva we found significant increases from baseline for guvacine (BN, BQ), arecoline (all groups), guvacoline (BN), arecaidine (all groups), nicotine (BQ), and chavibetol (BL, BQ), and significant differences between all groups for total areca-specific alkaloids, total tobacco-specific alkaloids and chavibetol. From this pilot study, we propose the following chemical patterns as biomarkers: areca alkaloids for BN use, areca alkaloids and chavibetol for BL use, and areca alkaloids plus chavibetol and tobacco-specific alkaloids for BQ use.